Effects of outdoor sports on college students’ learning burnout: a multiple mediation model of social support and self-regulation - Xu, Peng (Frontiers in Psychology, 2025)
ObjectiveThis study investigates the alleviating effect of outdoor sports on learning burnout among university students, focusing on the mediating roles of social support and self-regulation ability.MethodsA cross-sectional survey was conducted with 942 university students in China. Structural Equation Modeling (SEM) was employed to explore the direct and indirect effects of outdoor sports on learning burnout.ResultsThe results revealed that outdoor sports negatively predicted learning burnout both directly and indirectly. Social support and self-regulation ability were found to partially mediate this relationship. Additionally, a significant chain mediation effect was identified, where outdoor sports enhanced social support, which in turn fostered self-regulation, ultimately reducing learning burnout.ConclusionThe findings highlight the importance of integrating outdoor sports into mental health and academic support strategies. This study contributes to a deeper understanding of how external and internal psychological resources interact to reduce academic stress and promote well-being.